Settlement of Funing Natural Clays under 14-Year Embankment Loads: A Case Study - Heng Wang; Ling-Ling Zeng; Jian-Wen Ding; Zhen-Shun Hong (Advances in Civil Engineering)
The settlement behavior of soft natural clays under a 14-year embankment load is investigated by obtaining the high-quality undisturbed samples of soft natural clays beneath a constructed embankment. It is found that the conditional way of determining the settlement by combining the layerwise summation method of calculating settlement, the Osterberg method of determining the embankment load-induced stress in subsoil, and the compression parameters determined from high-quality undisturbed samples overestimates the settlement, compared with the field observations. The key cause is that the Osterberg method overestimates the vertical superimposed stress in this case. The modified method of determining the vertical stress in subsoil suggested by the authors is adopted for improving the accuracy of vertical superimposed stress calculated. The balance among errors in the settlement calculation model, determination of vertical superimposed stress induced by embankment loads, and measurement of compression parameters are also discussed.